2017
DOI: 10.7554/elife.26990
|View full text |Cite
|
Sign up to set email alerts
|

Actin-based protrusions of migrating neutrophils are intrinsically lamellar and facilitate direction changes

Abstract: Leukocytes and other amoeboid cells change shape as they move, forming highly dynamic, actin-filled pseudopods. Although we understand much about the architecture and dynamics of thin lamellipodia made by slow-moving cells on flat surfaces, conventional light microscopy lacks the spatial and temporal resolution required to track complex pseudopods of cells moving in three dimensions. We therefore employed lattice light sheet microscopy to perform three-dimensional, time-lapse imaging of neutrophil-like HL-60 c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 61 publications
4
111
0
Order By: Relevance
“…Movie 5). While the front of migrating leukocytes usually displays lamellar shaped protrusions 32 , CK666-treated cells formed filopodia and blebs in the cell front. The effect of CK666 on swimming speed was found intermediate between blebbistatin and Latrunculin cases.…”
Section: Resultsmentioning
confidence: 97%
“…Movie 5). While the front of migrating leukocytes usually displays lamellar shaped protrusions 32 , CK666-treated cells formed filopodia and blebs in the cell front. The effect of CK666 on swimming speed was found intermediate between blebbistatin and Latrunculin cases.…”
Section: Resultsmentioning
confidence: 97%
“…An example is lightsheet microscopy of neutrophils crawling through collagen filaments 20 imaged once per second for 3 minutes, with and without motility-affecting drugs. To examine whether the cells propel themselves by pushing or pulling on filaments, we can measure displacements of collagen in contact with cells (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, it is interesting to speculate that CH1-CH2 domains could be used to engineer probes for different structural states of f-actin for use both in vitro and in vivo. In fact, although utrnWT has been commonly used as a marker for f-actin (Burkel et al, 2007), it has also been reported to localize more preferentially to the trailing edge of migrating cells (Fritz-Laylin et al, 2017). Cterminal truncated forms of utrnWT have also been used for labelling of nuclear actin filaments (Belin et al, 2014) and direct fusions to GFP via a helical linker have been used in fluorescence polarization studies (Nakai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%